Research trends in corporate social responsibility and innovation: a bibliometric analysis - Chu, Mingyue; Muhamad, Haslinah; Mustapha, Mazlina; San, Ong Tze; Zan, Fangfang; Jia, Xiaoxiao (Mary Ann Liebert, 2022)
The relationship between corporate social responsibility (CSR) and innovation has received considerable attention in the last two decades. While several studies have explored the impact of CSR on innovation. While several studies have explored the impact of CSR on innovation, few studies have attempted to use bibliometric methods to analyze and visualize the evolution and trends in the CSR and innovation fields. In this research, 1279 Web of Science (WoS) published papers on CSR and innovation were collected and analyzed using VOSviwer, CiteSpace, and Bibliometrix R-package and the MK trend test. The analysis was conducted in terms of the number of articles published per year, most productive journals, authors, and countries, as well as collaboration between countries and authors, keyword analysis, co-citation clustering analysis, and research frontiers. The results showed that: (a) The MK trend test shows that the amount of CSR and innovation research is increasing. The top three journals in terms of productivity are Sustainability, Journal of Cleaner Production, and Corporate Social Responsibility and Environmental Management. The collaboration between authors forms a loose network and Ahmad, N has the most extensive network of international collaborations. There is close cooperation between countries, with a predominance of Asian, European, and North American collaborations, and the MK trend test shows that each country’s publications on the relationship between corporate social responsibility and innovation in the past 20 years have an obvious upward trend. (b) Through the analysis of keywords, it is necessary to research “corporate social responsibility”, “sustainability”, “innovation”, “financial performance “, and other topics associated with these themes. (c) The intellectual structure of CSR and innovation establishes five core clusters, including social innovation, CSR practice, sustainable global value chain, sustainable business model, and buyer–supplier collaboration. (d) Two forward-looking directions for future CSR and innovation research are proposed, and the limitations of the research are discussed.